Intergenerational Mobility A Study of Social Classes in India - Majumder, Rajarshi; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
Discrimination and exclusion in the process of capability formation and the labor market transcend the boundaries of the current generation and spill over to successive generations as well. Though a plethora of work has been done at the international level, the area has not been the focus of Indian economic research despite social exclusion and disparity having been quite substantial in India, especially the division along caste lines. The book addresses this research gap and explores the issue of intergenerational mobility across different social classes in the Indian context, analyzing the spheres of both education and occupation. We contend that parental education and occupation have a significantly greater impact on educational attainment and occupational choice for socially excluded groups compared to the advanced groups. In the labor market, intergenerational mobility is low and most of it is lateral and not vertical, increasing the possibility of discrimination in the labor market. This book highlights the fact that the long history of social exclusion has had a lasting effect and it is very difficult to come out of this inertia.
Chapter 1: Introduction -- Chapter 2: Education and Occupation in India -- Chapter 3: Intergenerational Mobility -- Chapter 4: Inertia across Generations -- Chapter 5: Regional Dimensions of Mobility -- Chapter 6: Intergenerational Mobility: Micro Level Study -- Chapter 7: State Support and Occupational Change -- Chapter 8: Conclusion.
Keywords: Economics; Literacy; Development Economics; Labor economics; Economics/Management Science; Labor Economics; Social Structure, Social Inequality; Development Economics; Literacy